Unaccustomed Earth - Lahiri, Jhumpa (Gurugram: Penguin Random House, 2008)
In the stunning title story, Ruma, a young mother in a new city, is visited by her father, who carefully tends the earth of her garden, where he and his grandson form a special bond. But he$1 (Bs harboring a secret from his daughter, a love affair he$1 (Bs keeping all to himself. In (3z(BA Choice of Accommodations,(3y (Ba husband$1 (Bs attempt to turn an old friend$1 (Bs wedding into a romantic getaway weekend with his wife takes a dark, revealing turn as the party lasts deep into the night. In (3z(BOnly Goodness,(3y (Ba sister eager to give her younger brother the perfect childhood she never had is overwhelmed by guilt, anguish, and anger when his alcoholism threatens her family. And in (3z(BHema and Kaushik,(3y (Ba trio of linked stories$1 (Ba luminous, intensely compelling elegy of life, death, love, and fate$1 (Bwe follow the lives of a girl and boy who, one winter, share a house in Massachusetts. They travel from innocence to experience on separate, sometimes painful paths, until destiny brings them together again years later in Rome.s
Keywords: Fiction -- Interpersonal relations -- Immigrants$1 (BUnited Statess -- East Indian Americans; Short stories -- Children of immigrants